A Proposed Model for Integrated Low-Vision Rehabilitation Services in Canada. Issue 1 (January 2016) - Leat, Susan J.
ABSTRACT: Purpose: The provision and funding of low-vision rehabilitation (LVR) are very variable across Canada. Quebec is well served by 14 government-funded rehabilitation centers. In most provinces, there are no such multidisciplinary services—optometrists offer LVR from their offices to a greater or lesser degree or undertake assessments in centers run by CNIB (formerly Canadian National Institute for the Blind). No integrated model for LVR exists across Canada. This document proposes such a model, which focuses on the profession of optometry, but may also be applicable to ophthalmology. Methods: This article describes different models of LV provision, the evidence for their relative effectiveness, the current situation in Canada, including the variability between areas and the need to increase referrals to LVR, and the current international consensus for LV provision. With the projected increase in people with LV, a generally accepted LV model for Canada is required to improve patient care. Results: It has become recognized in the global community that a tiered system may be required to provide for patients who range in their visual rehabilitation needs and geographic locations. The proposed LVR model includes three levels: 1. Screening/recognition of a potential patient with LV followed by appropriate triage. All optometrists should be involved at this level. 2. Management of the patient with minimum visual impairment/disability. This level of LVR can take place in a local optometry office with a minimal of extra equipment or devices. Level 3: Comprehensive LVR for patients with more vision loss and greater disabilities. Level 3 requires collaboration with other professionals, and three mechanisms are proposed by this which may take place. Conclusions: The proposed model is expected to be useful for future education, policy decisions, and collaboration in Canada, and it may also be of interest for the development of LV services in other countries.